POLTERGEIST PHENOMENA IN CONTEMPORARY FOLKLORE - Oana, VOICHICI (Editura Muzeul National al Literaturii Romane, 2018)
The article deals with instances of the supernatural in Romanian urban legends, namely what we call the strigoi , or poltergeist. Usually, folklorists tend to exclude the supernatural f rom the category of urban legends, however we have decided to take these accounts into consideration based on the fact that the transmitter, the narrators do not distinguish between these elements and the rest of contemporary legends and today’s popular cu lture abounds in such accounts.